Application of neural networks for structure updating - Miller, Bartosz (Computer Assisted Methods in Engineering and Science, 2011)
The paper presents the application of Artificial Neural Networks (ANNs) for finite element (FE) models updating. The investigated structures are beams and frames, their models are updated by ANNs with input vectors composed of dynamic characteristics of structures measured on laboratory models. The ANNs (multi layer feed-forward networks and Bayesian neural networks) are trained on numerical data disturbed by an artificial noise. The responses of the structures are measured on laboratory models. The updating procedure is also applied in identification of defects or additional masses attached to the structure